Off-road vehicle dynamics : analysis, modelling and optimization - Taghavifar, Hamid; Mardani, Aref (Springer, 2016)
This book deals with the analysis of off-road vehicle dynamics from kinetics and kinematics perspectives and the performance of vehicle traversing over rough and irregular terrain. The authors consider the wheel performance, soil-tire interactions and their interface, tractive performance of the vehicle, ride comfort, stability over maneuvering, transient and steady state conditions of the vehicle traversing, modeling the aforementioned aspects and optimization from energetic and vehicle mobility perspectives. This book brings novel figures for the transient dynamics and original wheel terrain dynamics at on-the-go condition.
Keywords: Off-road vehicles -- Dynamics.; elektronické knihy; electronic books